CHARACTER EDUCATION IN THE FRAMEWORK OF THE INDEPENDENT CURRICULUM: A COMPARATIVE ANALYSIS OF MODERN BOARDING SCHOOL AND GENERAL BOARDING SCHOOL - Fauzi, Abi; Sudin, Mahmudin (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2025)
This study aims to compare the implementation of character education within the framework of the Merdeka Curriculum as practiced in modern pesantren and boarding school pesantren. The Merdeka Curriculum was developed as a response to 21st-century educational challenges, emphasizing the Pancasila Student Profile, which consists of six key dimensions: faith and piety, global diversity, cooperation, independence, critical reasoning, and creativity. Character education is embedded in various subjects, particularly Religious Education and Civic Education, and reinforced through school culture and habituation. Boarding school models, including pesantren-based institutions, offer a conducive environment where academic learning and character formation are integrated within a residential setting. This qualitative study employs a library research method by analyzing books, scientific journal articles, and policy documents related to character education and curriculum implementation. The study presents a comparative analysis of character education practices in modern pesantren and general boarding schools. It highlights that modern pesantren emphasize spiritual and moral values through religious-based habituation and kyai leadership, while boarding schools implement structured, programmatic approaches to foster discipline and personal development. The synthesis of both models offers valuable insights for strengthening character education in line with the holistic goals of the Merdeka Curriculum.